Factors influencing sustainable entrepreneurial practices: Looking at individual-level factors through conventional entrepreneurial perspectives. - Sharif Hossain (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Entrepreneurs contribute to the economic and non-economic development of a country with their entrepreneurial activities, but they also negatively impact the environment. Using entrepreneurial capabilities, however, entrepreneurs can turn various social and environmental issues into profitable solutions to benefit society and ensure their long-term business success which is called sustainable entrepreneurship. Design/methodology/approach: This research aims to identify and highlight individual level factors that directly, or indirectly, affect individuals’ behaviour, and can influence them to engage in sustainable entrepreneurial activities. Findings: This secondary research reviewed and integrated existing literature to highlight individual-level factors that can influence entrepreneurs to engage in sustainable entrepreneurial practices. The insight of this paper could open key considerations for researchers in the sustainable entrepreneurship field to explore individual-level factors and enhance further understanding Paper type: Research paper